2019
DOI: 10.3390/ijms20051004
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Compartmentalization of Specific Integrin Heterodimers in Mouse Sperm

Abstract: Integrins are transmembrane cell receptors involved in two crucial mechanisms for successful fertilization, namely, mammalian intracellular signaling and cell adhesion. Integrins α6β4, α3β1 and α6β1 are three major laminin receptors expressed on the surface of mammalian cells including gametes, and the presence of individual integrin subunits α3, α6, β1 and β4 has been previously detected in mammalian sperm. However, to date, proof of the existence of individual heterodimer pairs in sperm and their detailed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In our previous study, we showed a presence of both α6β1 and α6β4 integrin heterodimers on sperm 20 . However, the α6 subunit preferentially creates the α6β4 heterodimer in the presence of both β4 and β1 subunits 23,51,52 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous study, we showed a presence of both α6β1 and α6β4 integrin heterodimers on sperm 20 . However, the α6 subunit preferentially creates the α6β4 heterodimer in the presence of both β4 and β1 subunits 23,51,52 .…”
Section: Discussionmentioning
confidence: 80%
“…With the ability of tetraspanins being part of signalling cascades involving cytoskeleton 5,15,16 they also play a crucial role in the organization of functional membrane protein cluster domains called a tetraspanin web, which were also described in oocyte and recently in sperm. The integral part of the tetraspanin web are integrins and the presence of α3β1, α6β1 and α6β4 integrins was shown in sperm [17][18][19][20] . Importantly, in somatic cells, tetraspanin CD151 was found to play a key role in regulating the adhesion strengthening of integrin α6β1 21 .…”
mentioning
confidence: 99%
“…The adhesion molecule trophinin was shown to be associated with sperm motility in humans (Hatakeyama et al, 2008) and mice (Park et al, 2012). Once sperm arrive at the oviducts, adhesion molecules facilitate the attachment of sperm to the oviductal epithelium (Aviles, Gutierrez‐Adan, & Coy, 2010; Frolikova et al, 2016, 2019; Talevi & Gualtieri, 2010). This is an important step that prevents premature capacitation in sperm.…”
Section: Adhesion Molecules and Reproductionmentioning
confidence: 99%
“…Once sperm arrive at the oviducts, adhesion molecules facilitate the attachment of sperm to the oviductal epithelium (Aviles, Gutierrez-Adan, & Coy, 2010;Frolikova et al, 2016Frolikova et al, , 2019Talevi & Gualtieri, 2010). This is an important step that prevents premature capacitation in sperm.…”
Section: Gamete Transportmentioning
confidence: 99%
“…In addition to capacitation-associated signaling pathways in the sperm flagellum, super-resolution has been employed to investigate the acrosome reaction. Namely, it has revealed changes in the actin cytoskeleton in the sperm head ( Figure 6E) [228], the distribution of specific integrin heterodimers [234,235], and the formation of SNARE protein complexes immediately prior to acrosome exocytosis [236]. 3D STORM has also revealed unique structures in sperm cells.…”
Section: Novel Technology To Study Trafficking Of Proteins (Super-resmentioning
confidence: 99%